2017
DOI: 10.1038/s41598-017-07737-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic predisposition to lung cancer: comprehensive literature integration, meta-analysis, and multiple evidence assessment of candidate-gene association studies

Abstract: More than 1000 candidate-gene association studies on genetic susceptibility to lung cancer have been published over the last two decades but with few consensuses for the likely culprits. We conducted a comprehensive review, meta-analysis and evidence strength evaluation of published candidate-gene association studies in lung cancer up to November 1, 2015. The epidemiological credibility of cumulative evidence was assessed using the Venice criteria. A total of 1018 publications with 2910 genetic variants in 754… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 54 publications
(59 reference statements)
0
63
0
5
Order By: Relevance
“…Jabir and Hoidy found that individuals carrying the CT genotype of SOD2 ‐rs4880 manifested an increased risk of breast cancer (in dominant model) . Moreover, meta‐analysis performed by Wang et al showed that rs4880 was significantly associated with lung cancer susceptibility . The protective role of rs4880 against pancreatic cancer was identified by Zhang et al In addition, the effect of rs4880 on risk of oral squamous cell carcinoma gastric cancer progression and tumor aggressiveness was also reported previously.…”
Section: Discussionmentioning
confidence: 83%
“…Jabir and Hoidy found that individuals carrying the CT genotype of SOD2 ‐rs4880 manifested an increased risk of breast cancer (in dominant model) . Moreover, meta‐analysis performed by Wang et al showed that rs4880 was significantly associated with lung cancer susceptibility . The protective role of rs4880 against pancreatic cancer was identified by Zhang et al In addition, the effect of rs4880 on risk of oral squamous cell carcinoma gastric cancer progression and tumor aggressiveness was also reported previously.…”
Section: Discussionmentioning
confidence: 83%
“…To our knowledge, the association between miR34b/c and Wilms tumor susceptibility has not been investigated. miR34b/c has been shown to be intimately connected to the development and prognosis of a variety of tumors, including gastric cancer, bladder cancer, pancreatic cancer, ovarian cancer, prostate cancer, hepatocellular carcinoma, neuroblastoma and many others [31][32][33][34][35]. In our previous study, we found that miR34b/c rs4938723 T>C polymorphism has a protective effect on neuroblastoma [36].…”
Section: Discussionmentioning
confidence: 91%
“…Genes CRABP1, AGPHD1 (also called HYKK), and CHRNA3 are nearby the highly significant locus on chromosome 15, and have been identified in previous literature as potentially associated with lung cancer. AGPHD1 and CHRNA3 have been associated with lung cancer via GWAS‐type analyses (Wang et al, ), while CRABP1 has been associated with lung cancer via an analysis of messenger RNA (Favorskaya et al, ), providing further evidence that the dysregulation of CRABP1 affects lung cancer risk.…”
Section: Resultsmentioning
confidence: 99%